Human linker histones: interplay between phosphorylation and O-β-GlcNAc to mediate chromatin structural modifications - Nazar Shazia; Nazar Noreen; Shabbiri Khadija; Ahmad Waqar; Qaiser Saba; Shabbir Mughal Mirza (Cell Division, 2011)
Abstract Eukaryotic chromatin is a combination of DNA and histone proteins. It is established fact that epigenetic mechanisms are associated with DNA and histones. Initial studies emphasize on core histones association with DNA, however later studies prove the importance of linker histone H1 epigenetic. There are many types of linker histone H1 found in mammals. These subtypes are cell specific and their amount in different types of cells varies as the cell functions. Many types of post-translational modifications which occur on different residues in each subtype of linker histone H1 induce conformational changes and allow the different subtypes of linker histone H1 to interact with chromatin at different stages during cell cycle which results in the regulation of transcription and gene expression. Proposed O-glycosylation of linker histone H1 promotes condensation of chromatin while phosphorylation of linker histone H1 is known to activate transcription and gene regulation by decondensation of chromatin. Interplay between phosphorylation and O-β-GlcNAc modification on Ser and Thr residues in each subtype of linker histone H1 in Homo sapiens during cell cycle may result in diverse functional regulation of proteins. This in silico study describes the potential phosphorylation, o-glycosylation and their possible interplay sites on conserved Ser/Thr residues in various subtypes of linker histone H1 in Homo sapiens.